Tom Sawyer and Huckleberry Finn - Twain, Mark, 1835-1910 (New York : Knopf, 1991)
All modern American literature comes from one book by Mark Twain called Huckleberry Finn . . . All American writing comes from that. There was nothing before. There has been nothing as good since. Ernest Hemingway As characters Tom and Huck have become American myths (a form of transubstantiation achieved by remarkably few fictional creations in the last hundred years), and that very fact indicates that whatever distinctions are made between the two novels, and however many reservations are cited about either or both, Twain possessed extraordinary imaginative power. from the Introduction by Miles Donald.
Includes bibliographical references (p. xxix).
Keywords: Sawyer, Tom (Fictitious character) -- Fiction; Finn, Huckleberry (Fictitious character) -- Fiction; Boys -- Fiction; Mississippi River -- Fiction; Missouri -- Fiction; Humorous fiction; Adventure fiction